2013
DOI: 10.1007/s00426-013-0486-8
|View full text |Cite
|
Sign up to set email alerts
|

Imagined own-body transformations during passive self-motion

Abstract: Spatial perspective taking is a crucial social skill that underlies many of our everyday interactions. Previous studies have suggested that spatial perspective taking is an embodied process that involves the integration of both motor and proprioceptive information. Given the importance of vestibular signals for own-body perception, mental own-body imagery, and bodily self-consciousness, in the present study we hypothesized that vestibular stimulation due to passive own-body displacements should also modulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 52 publications
4
55
0
1
Order By: Relevance
“…Passive whole-body yaw rotations (activating the horizontal semicircular canals) facilitated egocentric body-related mental imagery if actual rotations and shortest paths of mental rotation were side-congruent. While general bilateral vestibular loss in the study by Grabherr et al (2011), and GVS in the study by Lenggenhager et al (2008), involved altered vestibular signals from both otoliths and semicircular canals, the study by van Elk and Blanke (2014) showed that selective stimulation of the semicircular canal signals affected egocentric mental imagery.…”
Section: Part Two: Vestibular Contributions To Bodily Self-related Comentioning
confidence: 86%
See 2 more Smart Citations
“…Passive whole-body yaw rotations (activating the horizontal semicircular canals) facilitated egocentric body-related mental imagery if actual rotations and shortest paths of mental rotation were side-congruent. While general bilateral vestibular loss in the study by Grabherr et al (2011), and GVS in the study by Lenggenhager et al (2008), involved altered vestibular signals from both otoliths and semicircular canals, the study by van Elk and Blanke (2014) showed that selective stimulation of the semicircular canal signals affected egocentric mental imagery.…”
Section: Part Two: Vestibular Contributions To Bodily Self-related Comentioning
confidence: 86%
“…Natural vestibular stimulation can be experimentally induced by head accelerations, e.g., by passive whole-body rotation or translation (e.g., Prsa et al, 2012; van Elk and Blanke, 2014) that are sensed by the semicircular canals or otolith organs respectively. Natural vestibular stimulation may be given under terrestrial conditions by constant gravitational forces due to the attraction exerted by the earth on mass.…”
Section: Part One: the Vestibular System And Bodily Self-consciousnesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive processes with a clear spatial component include mental space representation such as the mental number line (Hartmann et al, 2012; Ferre et al, 2013b) and mental body transformation or perspective-taking (Lenggenhager et al, 2008; Falconer and Mast, 2012; Van Elk and Blanke, 2014). Several studies have investigated whether vestibular sensations influence mental space and movement representations.…”
Section: “What” and “When” To Stimulate The Vestibular Systemmentioning
confidence: 99%
“…Originally conceived as a primary system embedded into reflex generation for spinal and ocular-motor control, there is now an exciting and rapidly growing line of research showing that the vestibular system—which is intrinsically highly convergent with other sensory and motor signals (Angelaki and Cullen, 2008)—interacts with various cognitive processes such as spatial navigation (Angelaki et al, 2009), space perception (Ferre et al, 2013a), body representation (Lopez et al, 2010; Ferre et al, 2013c), mental imagery (Lenggenhager et al, 2008; Falconer and Mast, 2012; Van Elk and Blanke, 2014), attention (e.g., Figliozzi et al, 2005), memory (e.g., Smith et al, 2010), risk perception (Mckay et al, 2013), and even social cognition (Lopez et al, 2013). …”
mentioning
confidence: 99%